Supporting Researchers and Institutions in Engagement and Impact Assessment: A Gap Analysis Concerning the Core Skills of LIS Professionals in Australia. Issue 2 (3rd April 2017) - Nicholson, James
Abstract: Academic institutions have been evaluating research for many years. There has been a focus towards measuring and demonstrating research excellence in Australia with the Excellence in Research for Australia (ERA) replacing the Research Quality Framework in 2007. Since then Australia have moved to evaluate not just the quality of research but its impact beyond academia. The aim of this study is to investigate the skills needed by information professionals to guide researchers and universities in fulfilling their requirements of the EI Assessment that will be implemented alongside ERA 2018. This study will involve an inductive framework by using multiple analytical techniques. It will gather job adverts and role descriptions which are associated with research support in engagement and impact assessment. Through thematic coding, a content analysis will be conducted, identifying the core competencies required in these roles. This will lead to a gap analysis / mapping exercise to understand the relationship between expected and highly regarded core competencies required by employers to fulfil supporting roles in engagement and impact assessment, and the current level of skill expected by industry body the Australian Library and Information Association, via their research focused skills audit template.